Effects of non-antibiotic feed additives on performance, tibial dyschondroplasia incidence and tibia characteristics of broilers fed low-calcium diets. - Houshmand, A.; Kasim, Azhar; Idrus, Zulkifli; Bejo, Mohd Hair; Meimandipour, Amir; Kamyab, A. (Wiley, 2011)
This experiment was conducted to investigate and compare the efficacy of different feed additives on performance, tibial dyschondroplasia (TD) incidence and tibia characteristics of male broilers fed low-calcium diets. A completely randomized design, with six treatments and five replicates of five chicks per each was used. Experimental treatments were: (i) Basal diet containing recommended level of calcium (0.9%) as control treatment (Ctrl), (ii) low-calcium (0.67%) diet without any additive (LC), (iii) low-calcium diet + probiotic (2g/kg diet), (iv) low-calcium diet + prebiotic (2g/kg diet), (v) low-calcium diet + synbiotic [mix of probiotic and prebiotic (each 2g/kg diet)], (vi) low-calcium diet + organic acid (1.5g/kg diet). Birds were reared in an open-sided house system under natural tropical condition until 21days of age. Feeding with low-calcium diet negatively influenced broiler performance (body weight, body weight gain and feed conversion ratio) and tibia characteristics, whereas dietary inclusion of all feed additives had beneficial effects on above-mentioned parameters and helped the birds to overcome problems related to low-calcium diets. Different treatments had no effect on TD incidence.